Lipocalin 2 Protects Against Escherichia coli Infection by Modulating Neutrophil and Macrophage Function - Wang, Qianqian; Li, Shuhui; Tang, Xueyou; Liang, Li; Wang, Fengqin; Du, Huahua (Frontiers in Immunology, 2019)
Lipocalin 2 (Lcn2) is an essential component of the antimicrobial innate immune system. It attenuates bacterial growth by binding and sequestering the iron-scavenging siderophores to prevent bacterial iron acquisition. Whereas the ability of Lcn2 to sequester iron is well described, the role of Lcn2 in regulating immune cells during bacterial infection remains unclear. In this study, we showed that upon infection with Escherichia coli (E. coli O157:H7), Lcn2-deficient mice (Lcn2-/- mice) carried more bacteria in blood and liver, and the acute phase sera lost their antibacterial activity in vitro. Neutrophils from Lcn2-/- mice were defective in homeostasis and morphological development. After E. coli O157:H7 infection, neutrophils in Lcn2-/- mice reduced their migration capacity with 30% reduction of extravasated neutrophils, and impaired their chemotaxis by reducing the secretion of chemoattractants such as TNF-α, MCP-1 and MIP-2, which are instrumental in eliciting a neutrophil response. Additionally, we also found that some secreted cytokines (IL-6, IL-1, TNF-) were decreased, as well as transcripts of inflammatory cytokines (IL-6, IL-1, TNF- and IL-10), chemokines (MIP-2 and MCP-1) and iNOS production were all strongly repressed in Lcn2-/- macrophages. Furthermore, Lcn2 could induce the production of chemokines, promote the migration and phagocytosis of macrophages. Thus, Lcn2 deficiency could impair the migration and chemotaxis ability of neutrophils, and disturb the normal secretion of inflammatory cytokines of macrophages. Therefore, the heightened sensitivity of Lcn2-/- mice to E. coli O157:H7 is not only due to the antibacterial function of Lcn2, but also a consequence of impaired functions of immune cells including neutrophils and macrophages.